The quantum Hall effect in an InAs/GaSb based electron-hole system and its current-driven breakdown - Takashina, K; Nicholas, R; Kardynal, B; Mason, N; Maude, D; Portal, J (2002)
We examine the quantum Hall effect in an electron-hole system and its current-driven breakdown, We find that samples with closely matched electron and hole concentrations have vastly reduced critical cur-rents while those with many more electrons than holes show much larger critical currents, though still smaller than those reported for single-carrier type systems, The channel width dependence shows two regimes of behaviour. States with larger critical cur-rents ( > 5 muA) have linear width dependence. while for narrower channel widths where the critical current is smaller, the critical current has a superlinear relationship with the channel width. (C) 2002 Elsevier Science B.V. All rights reserved.